# Ch 6.

6: The Convolution Integral
Sometimes it is possible to write a Laplace transform H(s) as
H(s) = F(s)G(s), where F(s) and G(s) are the transforms of
known functions f and g, respectively.
In this case we might expect H(s) to be the transform of the
product of f and g. That is, does
H(s) = F(s)G(s) = L{f }L{g} = L{f g}?
On the next slide we give an example that shows that this
equality does not hold, and hence the Laplace transform
cannot in general be commuted with ordinary multiplication.
In this section we examine the convolution of f and g, which
can be viewed as a generalized product, and one for which the
Laplace transform does commute.
Example 1
Let f (t) = 1 and g(t) = sin(t). Recall that the Laplace
Transforms of f and g are

Thus

and

Therefore for these functions it follows that
{ } { }
1
1
sin ) ( ) (
2
+
= =
s
t L t g t f L
{ } { } { } { }
1
1
sin ) ( ,
1
1 ) (
2
+
= = = =
s
t L t g L
s
L t f L
{ } { } { } ) ( ) ( ) ( ) ( t g L t f L t g t f L =
{ } { }
( ) 1
1
) ( ) (
2
+
=
s s
t g L t f L
Theorem 6.6.1
Suppose F(s) = L{f (t)} and G(s) = L{g(t)} both exist for
s > a > 0. Then H(s) = F(s)G(s) = L{h(t)} for s > a, where

The function h(t) is known as the convolution of f and g and
the integrals above are known as convolution integrals.

Note that the equality of the two convolution integrals can be
seen by making the substitution u = t - t.
The convolution integral defines a “generalized product” and
can be written as h(t) = ( f *g)(t). See text for more details.
} }
÷ = ÷ =
t t
d t g t f d g t f t h
0 0
) ( ) ( ) ( ) ( ) ( t t t t t
Example 2
Find the Laplace Transform of the function h given below.

Solution: Note that f (t) = t and g(t) = sin2t, with

Thus by Theorem 6.6.1,
4
2
} 2 {sin )} ( { ) (
1
} { )} ( { ) (
2
2
+
= = =
= = =
s
t L t g L s G
s
t L t f L s F
}
÷ =
t
d t t h
0
2 sin ) ( ) ( t t t
{ }
( ) 4
2
) ( ) ( ) ( ) (
2 2
+
= = =
s s
s G s F s H t h L
Example 3: Find Inverse Transform (1 of 2)
Find the inverse Laplace Transform of H(s), given below.

Solution: Let F(s) = 2/s
2
and G(s) = 1/(s - 2), with

Thus by Theorem 6.6.1,
{ }
{ }
t
e s G L t g
t s F L t f
2 1
1
) ( ) (
2 ) ( ) (
= =
= =
÷
÷
) 2 (
2
) (
2
÷
=
s s
s H
{ }
}
÷ = =
÷
t
d e t t h s H L
0
2 1
) ( 2 ) ( ) ( t t
t
Example 3: Solution h(t) (2 of 2)
We can integrate to simplify h(t), as follows.
| | | |
2
1
2
1
2
1
2
1
1
2
1
1
2 2 ) ( 2 ) (
2
2 2 2
2 2 2
0
2
0
2
0
2
0
2
0
2
0
2
÷ ÷ =
÷ + ÷ ÷ =
(
¸
(

¸

÷ ÷ ÷ ÷ =
(
¸
(

¸

÷ ÷ =
÷ = ÷ =
}
} } }
t e
e e t t te
e e t e t
d e e te
d e d e t d e t t h
t
t t t
t t t
t t t
t t t
t t
t t t t t
t t t
t t t
Find the solution to the initial value problem

Solution:

or

Letting Y(s) = L{y}, and substituting in initial conditions,

Thus
)} ( { } { 4 } { t g L y L y L = +
' '
| | ) ( } { 4 ) 0 ( ) 0 ( } {
2
s G y L y sy y L s = +
'
÷ ÷
Example 4: Initial Value Problem (1 of 4)
( ) ) ( 1 3 ) ( 4
2
s G s s Y s + ÷ = +
4
) (
4
1 3
) (
2 2
+
+
+
÷
=
s
s G
s
s
s Y
1 ) 0 ( , 3 ) 0 ( ), ( 4 ÷ =
'
= = +
' '
y y t g y y
We have

Thus

Note that if g(t) is given, then the convolution integral can be
evaluated.
t t t d g t t t t y
t
) ( ) ( 2 sin
2
1
2 sin
2
1
2 cos 3 ) (
0
}
÷ + ÷ =
Example 4: Solution (2 of 4)
) (
4
2
2
1
4
2
2
1
4
3
4
) (
4
1 3
) (
2 2 2
2 2
s G
s s s
s
s
s G
s
s
s Y
(
¸
(

¸

+
+
(
¸
(

¸

+
÷
(
¸
(

¸

+
=
+
+
+
÷
=
Recall that the Laplace Transform of the solution y is

Note u (s) depends only on system coefficients and initial
conditions, while + (s) depends only on system coefficients
and forcing function g(t).
Further, |(t) = L
-1
{u (s)} solves the homogeneous IVP

while ¢(t) = L
-1
{+ (s)} solves the nonhomogeneous IVP
Example 4:
Laplace Transform of Solution (3 of 4)
) ( ) (
4
) (
4
1 3
) (
2 2
s Ψ s Φ
s
s G
s
s
s Y + =
+
+
+
÷
=
1 ) 0 ( , 3 ) 0 ( ), ( 4 ÷ =
'
= = +
' '
y y t g y y
1 ) 0 ( , 3 ) 0 ( , 0 4 ÷ =
'
= = +
' '
y y y y
0 ) 0 ( , 0 ) 0 ( ), ( 4 =
'
= = +
' '
y y t g y y
Examining + (s) more closely,

The function H(s) is known as the transfer function, and
depends only on system coefficients.
The function G(s) depends only on external excitation g(t)
applied to system.
If G(s) = 1, then g(t) = o(t) and hence h(t) = L
-1
{H(s)} solves
the nonhomogeneous initial value problem

Thus h(t) is response of system to unit impulse applied at t = 0,
and hence h(t) is called the impulse response of system.
Example 4: Transfer Function (4 of 4)
4
1
) ( where ), ( ) (
4
) (
) (
2 2
+
= =
+
=
s
s H s G s H
s
s G
s Ψ
0 ) 0 ( , 0 ) 0 ( ), ( 4 =
'
= = +
' '
y y t y y o
Consider the general initial value problem

This IVP is often called an input-output problem. The
coefficients a, b, c describe properties of physical system,
and g(t) is the input to system. The values y
0
and y
0
' describe
initial state, and solution y is the output at time t.
Using the Laplace transform, we obtain

or
Input-Output Problem (1 of 3)
0 0
) 0 ( , ) 0 ( ), ( y y y y t g cy y b y a
'
=
'
= = +
'
+
' '
| | | | ) ( ) ( ) 0 ( ) ( ) 0 ( ) 0 ( ) (
2
s G s cY y s sY b y sy s Y s a = + ÷ +
'
÷ ÷
) ( ) (
) ( ) (
) (
2 2
0 0
s Ψ s Φ
c bs as
s G
c bs as
y a y b as
s Y + =
+ +
+
+ +
'
+ +
=
We have

As before, u (s) depends only on system coefficients and
initial conditions, while + (s) depends only on system
coefficients and forcing function g(t).
Further, |(t) = L
-1
{u (s)} solves the homogeneous IVP

while ¢(t) = L
-1
{+ (s)} solves the nonhomogeneous IVP
Laplace Transform of Solution (2 of 3)
0 0
) 0 ( , ) 0 ( , 0 y y y y cy y b y a
'
=
'
= = +
'
+
' '
0 ) 0 ( , 0 ) 0 ( ), ( =
'
= = +
'
+
' '
y y t g cy y b y a
0 0
) 0 ( , ) 0 ( ), ( y y y y t g cy y b y a
'
=
'
= = +
'
+
' '
) ( ) (
) ( ) (
) (
2 2
0 0
s Ψ s Φ
c bs as
s G
c bs as
y a y b as
s Y + =
+ +
+
+ +
'
+ +
=
Examining + (s) more closely,

As before, H(s) is the transfer function, and depends only on
system coefficients, while G(s) depends only on external
excitation g(t) applied to system.
Thus if G(s) = 1, then g(t) = o(t) and hence h(t) = L
-1
{H(s)}
solves the nonhomogeneous IVP

Thus h(t) is response of system to unit impulse applied at t = 0,
and hence h(t) is called the impulse response of system, with
Transfer Function (3 of 3)
0 ) 0 ( , 0 ) 0 ( ), ( =
'
= = +
'
+
' '
y y t cy y b y a o
c bs as
s H s G s H
c bs as
s G
s Ψ
+ +
= =
+ +
=
2 2
1
) ( where ), ( ) (
) (
) (
{ } t t t ¢ d g t h s G s H L t
t
) ( ) ( ) ( ) ( ) (
0
1
}
÷ = =
÷